2016
DOI: 10.1097/ijg.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Bilateral Glaucoma Laser Treatments in Ontario

Abstract: The increase in same-day bilateral trabeculoplasties coincided with the introduction of selective laser trabeculoplasty. The proportion of this practice remained constant for the last 3 years of the study period. In 2013, 56.7% of iridotomies and 38.5% of trabeculoplasties were performed as same-day bilateral procedures. We recommend comparison studies between same-day and sequential laser therapies to assess complication rates and patient satisfaction to provide an evidence-based treatment approach, as there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…There are limited data for comparing same-day bilateral laser trabeculoplasty and sequential therapy [31]. An analysis of the use of laser trabeculoplasty in Ontario during 2000–2013 showed that after the introduction of SLT, there was a coincident increase in the number of same-day bilateral laser trabeculoplasty procedures in patients with POAG (4.9-fold increase).…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data for comparing same-day bilateral laser trabeculoplasty and sequential therapy [31]. An analysis of the use of laser trabeculoplasty in Ontario during 2000–2013 showed that after the introduction of SLT, there was a coincident increase in the number of same-day bilateral laser trabeculoplasty procedures in patients with POAG (4.9-fold increase).…”
Section: Surgical Techniquementioning
confidence: 99%
“…An analysis of the use of laser trabeculoplasty in Ontario during 2000–2013 showed that after the introduction of SLT, there was a coincident increase in the number of same-day bilateral laser trabeculoplasty procedures in patients with POAG (4.9-fold increase). However, sequential therapy is typically considered safer, as it gives treating physicians opportunities to assess the efficacy and side effects of the procedure on one eye before treating the fellow eye [31]. …”
Section: Surgical Techniquementioning
confidence: 99%
“…Тем не менее отмечены воспалительные проявления со стороны переднего отрезка глаза после проведения процедуры [34,35]. Необходимо отметить преимущества СЛТ в ряде случаев не только перед традиционной хирургией глаукомы, но и перед местной гипотензивной терапией: амбулаторные условия ее проведения; использование исключительно местных обезболивающих капель [36]; минимальное количество интра-и послеоперационных осложнений; не исключаются повторные процедуры для достижения требуемого гипотензивного эффекта; быстрота выполнения; а также важность альтернативного гипотензивного лечения для пациентов, не переносящих лекарственные препараты; низкая стоимость лечения; минимальный реабилитационный период и эффективность процедуры на ранних стадиях глаукомы [37].…”
unclassified